Genetic and Biological Changes of Newcastle Disease Virus Due to The Development of Chicken Production System - ., Sudarisman (Indonesian Animal Sciences Society, 2009)
In many countries, Newcastle Disease (ND) is one of the most important diseases of poultry. It causes serious economic losses in poultry industry. Newcastle Disease or pseudo-fowl pest is a highly infectious viral disease that causes very high mortality (up to 100% in severe epidemics) in poultry and wild birds around the world. Newcastle Disease remains endemic in many regions and continues to severely limit poultry production in some developing countries. The disease is currently being controlled by routine vaccinations in many countries. However, it was reported that outbreaks of ND in vaccinated flocks often occur on the field may not only be due to differences in the antigenicity of the NDV wild field strains and vaccine strains, but could also be as a result of differences in pathogenicity and virulence between different strains used as vaccine seed in NDV vaccine production. Â Key words: Newcastle Disease virus, biological changes, genetic changes, chicken